Embodied Vulnerabilities in Literature and Film - Flores-Quesada, María Magdalena (Asociación española de estudios anglo-americanos, 2024)
En esta reseña crítica, se analiza el volumen Embodied VulnerAbilities in Literature and Film editado por Cristina M. Gámez-Fernández y Miriam Fernández-Santiago(Routledge, 2024), subrayando su aportación al debate contemporáneo en torno a la vulnerabilidad en la literatura y el cine. This critical review analyses the volume Embodied VulnerAbilities in Literature and Film, edited by Cristina M. Gámez-Fernández and Miriam Fernández-Santiago (Routledge, 2024), highlighting its contribution to the contemporary debate on vulnerability in literature and cinema.
Todo el número se encuentra disponible en open access.Copyright de los textos de los autores
Keywords: Vulnerability; Literary studies; Contemporary fiction; Film studies